2002
DOI: 10.1093/toxsci/65.2.276
|View full text |Cite
|
Sign up to set email alerts
|

Spinosad Insecticide: Subchronic and Chronic Toxicity and Lack of Carcinogenicity in CD-1 Mice

Abstract: The potential toxicologic and oncogenic effects of spinosad, a natural fermentation product with insecticidal properties, were investigated. The 13-week toxicity study consisted of groups of 10 CD-1 mice/sex provided diets containing 0, 0.005, 0.015, 0.045, or 0.12% spinosad (Study 1). The 0.12% group was terminated on Test Day 44 due to mortality and overt clinical signs of toxicity. An 18-month chronic oncogenicity study consisted of groups of 50 CD-1 mice/sex provided diets containing 0, 0.0025, 0.008, or 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 19 publications
5
22
0
1
Order By: Relevance
“…The observations in group 2 were similar to the results of Siddiqui et al, (2007) and Sasidhar Babu et al, (2014) in birds for a period of 28 and 90 days respectively. The observations in group 3 were in accordance with the results of Stebbins et al, (2002) in experimental mice for a period of 13 weeks.…”
Section: Biochemical Parameters Total Protein Concentration (G/dl)supporting
confidence: 86%
See 1 more Smart Citation
“…The observations in group 2 were similar to the results of Siddiqui et al, (2007) and Sasidhar Babu et al, (2014) in birds for a period of 28 and 90 days respectively. The observations in group 3 were in accordance with the results of Stebbins et al, (2002) in experimental mice for a period of 13 weeks.…”
Section: Biochemical Parameters Total Protein Concentration (G/dl)supporting
confidence: 86%
“…The observations in group 2 were in agreement with experimental results of in Kammon et al, (2010) and Mohany et al, (2012) in layer chicken and rats respectively in IM induced studies. Increased levels of ALP in group 3 were in agreement with Stebbins et al, (2002) and Yano et al, (2002). An elevated level of serum ALP in the present study might be due to toxicity of IM, SPD and its combination which triggered the process of inflammation in liver, kidney and other organs which were evidenced histopathologically.…”
Section: Serum Alkaline Phosphatase (Iu/l)supporting
confidence: 85%
“…The most notable effect of spinosad after subchronic exposure in rats is vacuolar degeneration [19]. Stebbins et al [38] found that mice given 0.015% spinosad had vacuolation in liver and kidney tissues. In addition, it is possible that malathion and spinosad, like several other insecticides, adversely affect the cytochrome P450 system or the mitochondrial membrane transport system of hepatocytes [17].…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that the myeloid bodies represent an adaptative response lysosomal in origin, usually associated with the binding of cationic amphiphilic drugs (CADs) to phospholipids in cellular membranes (Reasor and Kacew, 2001). Nevertheless, not only the CADs induce phospholipidosis; some authors report that different compounds such as the natural insecticide spinosad (Stebbins et al, 2002) and alkylphenols from Gingko biloba (Hecker et al, 2002) are able to develop this cellular disorder. Although the exact mechanism for the accumulation of the phospholipids in lysosomes is unknown, it may be due to the generation of indigestible drug-lipid complex, inhibition of lysosomal phospholipases or a combination of these possibilities (Halliwell, 1997).…”
Section: Discussionmentioning
confidence: 99%